THE EFFECTIVENESS OF USING STAD IN JUNIOR HIGH STUDENT READING COMPREHENSION - Nana Nurjanah (Universitas Muhammadiyah Lampung, 2022)
Reading is a parts of language acquisition communication of sharimg information and ideas. In fact many students in junior high still confuse what is reading.The objective of this research is to know the effectiveness of using STAD in student reading comprehension in procedure text. Reading comprehension is essentially the ability to understand what has been read. There is little point in being able to pronounce the words on a page if the words mean nothing to you. After the research finished the research and analyzed the data that obtained from the research, then some conclusion can be drawn. Based on the result of the analysis and computation of the data, the researcher concluded as STAD is effective in improving students’ comprehenssion of reading procedure text.